Belowground morphology as a clue for plant response to disturbance and productivity in a temperate flora - Klimešová, Jitka; Herben, Tomáš (The New phytologist, 2024)
Plants possess a large variety of nonacquisitive belowground organs, such as rhizomes, tubers, bulbs, and coarse roots. These organs determine a whole set of functions that are decisive in coping with climate, productivity, disturbance, and biotic interactions, and have been hypothesized to affect plant distribution along environmental gradients. We assembled data on belowground organ morphology for 1712 species from Central Europe and tested these hypotheses by quantifying relationships between belowground morphologies and species optima along ecological gradients related to productivity and disturbance. Furthermore, we linked these data with species co-occurrence in 30 115 vegetation plots from the Czech Republic to determine relationships between belowground organ diversity and these gradients. The strongest gradients determining belowground organ distribution were disturbance severity and frequency, light, and moisture. Nonclonal perennials and annuals occupy much smaller parts of the total environmental space than major types of clonal plants. Forest habitats had the highest diversity of co-occurring belowground morphologies; in other habitats, the diversity of belowground morphologies was generally lower than the random expectation. Our work shows that nonacquisitive belowground organs may be partly responsible for plant environmental niches. This adds a new dimension to the plant trait spectrum, currently based on acquisitive traits (leaves and fine roots) only.
Keywords: podnebí; rostliny; Evropa; nonclonal perennials; environmental gradients; clonal growth organs; ekosystém; annuals; plant communities; Ecosystem; lesy; Europe; Plants; Forests; Climate